MENTAL HEALTH LEGISLATION: DOES IT PROTECT THE RIGHTS OF PEOPLE WITH MENTAL HEALTH PROBLEMS? - Simpson, Barbara; Chipps, Jennifer (Social Work/Maatskaplike Werk, 2012)
The International Federation of Social Work places a concern with human rights and social justice at the core of its definition of social work. Social work values are based on “respect for the equality, dignity and worth of all people” (IFSW, 2000), and social work practice has a special concern for vulnerable and oppressed people. People with mental health problems are amongst the most vulnerable members of society and in South Africa they comprise a considerable proportion of our society. According to the South African Stress and Health Survey (Herman, Steyn, Seedat, Heeringa, Moonal & Williams, 2009), the lifetime prevalence for any mental health problems in South Africa is 30.3% and neuropsychiatric disorders rank third in their contribution to the burden of disease in South Africa (Bradshaw, Norman & Schneider, 2007).